Social aspects, pre and post collapse of the Fundão dam, in the Doce river basin, Brazil - Gomes, Vanielle Aparecida Patrocinio; Jankowsky, Mayra; Carvalho, Raphaela Martins de; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2021)
The Rio Doce River Basin, located in southeastern Brazil, has a population of 3.5 million inhabitants, most of whom depend on the Rio Doce, considered one of the most important rivers in the country. But in 2015 this river was hit by one of the biggest socio-environmental disasters, the rupture of the Fundão dam in Mariana (MG). The mentioned population was exposed to the mud which severely impacted their lives. Thus, the objective is to carry out a bibliometric study (quantitative and qualitative), focusing on the social aspects that involve the Rio Doce Basin, seeking to verify and describe the changes that occurred in the publications before and after the disaster. Where 81 articles were analyzed that involve the general social aspects related to the Rio Doce Hydrographic Basin. It is possible to note that the disruption of the Fundão dam impacted the environment, society and the focus of research involving the basin. It was concluded that the publications on education, health and social impacts started to focus on the reality of those affected, as well as the isolated communities that suffer until today, five years after the disaster, with the remains of the mud. We highlight the works related to general social aspects, and the impacts on the riverside communities, in addition to discussing the actors involved, such as the State, companies, the Renova Foundation and those affected. Not forgetting to mention the importance of publications dealing with risks and failures in dams, in order to study ways to prevent and mitigate these types of disasters.